Self-efficacy strategies to improve exercise in patients with heart failure: A systematic review - Fatemeh Rajati; Masoumeh Sadeghi; Awat Feizi; Golamreza Sharifirad; Tolu Hasandokht; Firoozeh Mostafavi (ARYA Atherosclerosis, 2014)
BACKGROUND: Despite exercise is recommended as an adjunct to medication therapy in patients with heart failure (HF), non-adherence to exercise is a major problem. While improving self-efficacy is an effective way to increase physical activity, the evidence concerning the relationship between strategies to enhance self-efficacy and exercise among HF has not been systematically reviewed. The objective of this systematic review is to assess the effect of interventions to change the self-efficacy on exercise in patients with HF. METHODS: A systematic database search was conducted for articles reporting exercise self-efficacy interventions. Databases such as PubMed, ProQuest, CINAHL, Scopus, and PsycINFO, and the Cochrane Library were searched with restrictions to the years 2000-June 2014. A search of relevant databases identified 10 studies. Published randomized controlled intervention studies focusing strategies to change self-efﬁcacy to exercise adherence in HF were eligible for inclusion. In addition, studies that have applied self-efficacy-based interventions to improve exercise are discussed. RESULTS: Limited published data exist evaluating the self-efficacy strategies to improve exercise in HF. Dominant strategies to improve patients’ self-efficacy were performance accomplishments, vicarious experience, verbal persuasion, emotional arousal. CONCLUSION: Evidence from some trials supports the view that incorporating the theory of self-efficacy into the design of an exercise intervention is beneficial. Moreover, exercise interventions aimed at integrating the four strategies of exercise self-efficacy can have positive effects on confidence and the ability to initiate exercise and recover HF symptoms. Findings of this study suggest that a positive relationship exists between self-efficacy and initiating and maintaining exercise in HF, especially in the short-term period.